We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+8
855
6
avatar+575 

In the following fighure ,if triangle ABC is a right triangle,angle A= 90 degrees,point D located on AC ,point E is loacted on BC, $${\mathtt{AB}} = {\frac{{\mathtt{1}}}{{\mathtt{2}}}}{\mathtt{\,\times\,}}{\mathtt{BD}}$$ ,and $${\mathtt{CE}} = {\frac{{\mathtt{1}}}{{\mathtt{4}}}}{\mathtt{\,\times\,}}{\mathtt{EB}}$$. angle BDE=120 degrees,CD=3, then BC=?

 Jun 24, 2015

Best Answer 

 #1
avatar+22484 
+18

In the following fighure ,if triangle ABC is a right triangle,angle A= 90 degrees,point D located on AC ,point E is loacted on BC, $${\mathtt{AB}} = {\frac{{\mathtt{1}}}{{\mathtt{2}}}}{\mathtt{\,\times\,}}{\mathtt{BD}}$$ ,and $${\mathtt{CE}} = {\frac{{\mathtt{1}}}{{\mathtt{4}}}}{\mathtt{\,\times\,}}{\mathtt{EB}}$$. angle BDE=120 degrees,CD=3, then BC=?

 

We define:  CD = 3,  AB = y,   DB = 2y,   CE = x,   EB =  4x,   BC = 5x,   ED = u,   DA = d

1. Pythagoras:

$$\small{\overline{AB}^2 + \overline{DA}^2 = \overline{DB}^2}\\
\small{y^2+d^2=4y^2\qquad d^2 = 3y^2 \qquad d = \sqrt{3}y }$$

 

2. Pythagoras:

$$\small{\overline{CA}^2 + \overline{AB}^2 = \overline{BC}^2 \qquad \overline{CA} = 3+\sqrt{3}y}\\\\
\small{ (3+\sqrt{3}y)^2+y^2=(5x)^2\qquad \cdots \qquad
\boxed{x = \dfrac{ \sqrt{ 4y^2+6\sqrt{3}y+9 } } {5} ~~(1) }}$$

 

3. cos-rule:

$$\small{u^2 = 3^2 + x^2 - 2\cdot 3\cdot x \cdot \cos{(C)}\qquad \cos{(C)} = \dfrac{ 3 + \sqrt{3}y }{5x} \quad \cdots \quad \boxed{ u = \sqrt{x^2-1.2\sqrt{3}+5.4} ~~(2)}}$$

4. cos-rule:

$$\small{
\begin{array}{lcl}
(4x)^2 = u^2+(2y)^2-2u2y\cos{ (120\ensurement{^{\circ}}) } \quad \cos{(120\ensurement{^{\circ}}) } = -\frac{1}{2} \quad \cdots \quad 16x^2=u^2+4y^2+2uy \\
\text{we substitute u, formula (2)}\\
\cdots\\
15x^2 = -1.2\sqrt{3}y+5.4+4y^2+2y\sqrt{x^2-1.2\sqrt{3}y+5.4}\\
\text{we substitute first x, formula (1)}\\
\cdots\\
\frac{12}{5}y^2+}\frac{18}{5}\sqrt{3}y=4y^2-1.2\sqrt{3}y+2y\sqrt{x^2-1.2\sqrt{3}y+5.4} \qaud | \quad :y \\
\frac{12}{5}y+}\frac{18}{5}\sqrt{3}=4y-1.2\sqrt{3}+2\sqrt{x^2-1.2\sqrt{3}y+5.4} \\
\cdots\\
x^2-1.2\sqrt{3}y+5.4=(2.4\sqrt{3}-0.8y)^2\\
\text{we substitute again x, formula (1)}\\
\cdots\\
0.16y^2+0.24\sqrt{3}y+0.36-1.2\sqrt{3}y+5.4=17.28-3.84\sqrt{3}y+0.64y^2\\
0.48y^2-2.88\sqrt{3}y+11.52=0 \quad | :0.48 \quad \\
\boxed{y^2-6\sqrt{3}+24 = 0} \\\\
y_{1,2} = \frac{6\sqrt{3}\pm \2\sqrt{3}}{2}\\
y_1 = 4\sqrt{3} \quad \text{no solution}\\
y_2 = 2\sqrt{3} \quad \text{solution}\\\\
x = \dfrac{ \sqrt{ 4y^2+6\sqrt{3}y+9 } } {5} \\\\
x = \dfrac{ \sqrt{ 4 (2\sqrt{3})^2+6\sqrt{3}( 2\sqrt{3})+9 } } {5} \\\\
x = \dfrac{ \sqrt{ 48 +36+9 } } {5} \\\\
x = 1.92873015220\\\\
\mathbf{ \overline{BC} =5x = 9.64365076099 }
\end{array}
}$$

 

 Jun 24, 2015
 #1
avatar+22484 
+18
Best Answer

In the following fighure ,if triangle ABC is a right triangle,angle A= 90 degrees,point D located on AC ,point E is loacted on BC, $${\mathtt{AB}} = {\frac{{\mathtt{1}}}{{\mathtt{2}}}}{\mathtt{\,\times\,}}{\mathtt{BD}}$$ ,and $${\mathtt{CE}} = {\frac{{\mathtt{1}}}{{\mathtt{4}}}}{\mathtt{\,\times\,}}{\mathtt{EB}}$$. angle BDE=120 degrees,CD=3, then BC=?

 

We define:  CD = 3,  AB = y,   DB = 2y,   CE = x,   EB =  4x,   BC = 5x,   ED = u,   DA = d

1. Pythagoras:

$$\small{\overline{AB}^2 + \overline{DA}^2 = \overline{DB}^2}\\
\small{y^2+d^2=4y^2\qquad d^2 = 3y^2 \qquad d = \sqrt{3}y }$$

 

2. Pythagoras:

$$\small{\overline{CA}^2 + \overline{AB}^2 = \overline{BC}^2 \qquad \overline{CA} = 3+\sqrt{3}y}\\\\
\small{ (3+\sqrt{3}y)^2+y^2=(5x)^2\qquad \cdots \qquad
\boxed{x = \dfrac{ \sqrt{ 4y^2+6\sqrt{3}y+9 } } {5} ~~(1) }}$$

 

3. cos-rule:

$$\small{u^2 = 3^2 + x^2 - 2\cdot 3\cdot x \cdot \cos{(C)}\qquad \cos{(C)} = \dfrac{ 3 + \sqrt{3}y }{5x} \quad \cdots \quad \boxed{ u = \sqrt{x^2-1.2\sqrt{3}+5.4} ~~(2)}}$$

4. cos-rule:

$$\small{
\begin{array}{lcl}
(4x)^2 = u^2+(2y)^2-2u2y\cos{ (120\ensurement{^{\circ}}) } \quad \cos{(120\ensurement{^{\circ}}) } = -\frac{1}{2} \quad \cdots \quad 16x^2=u^2+4y^2+2uy \\
\text{we substitute u, formula (2)}\\
\cdots\\
15x^2 = -1.2\sqrt{3}y+5.4+4y^2+2y\sqrt{x^2-1.2\sqrt{3}y+5.4}\\
\text{we substitute first x, formula (1)}\\
\cdots\\
\frac{12}{5}y^2+}\frac{18}{5}\sqrt{3}y=4y^2-1.2\sqrt{3}y+2y\sqrt{x^2-1.2\sqrt{3}y+5.4} \qaud | \quad :y \\
\frac{12}{5}y+}\frac{18}{5}\sqrt{3}=4y-1.2\sqrt{3}+2\sqrt{x^2-1.2\sqrt{3}y+5.4} \\
\cdots\\
x^2-1.2\sqrt{3}y+5.4=(2.4\sqrt{3}-0.8y)^2\\
\text{we substitute again x, formula (1)}\\
\cdots\\
0.16y^2+0.24\sqrt{3}y+0.36-1.2\sqrt{3}y+5.4=17.28-3.84\sqrt{3}y+0.64y^2\\
0.48y^2-2.88\sqrt{3}y+11.52=0 \quad | :0.48 \quad \\
\boxed{y^2-6\sqrt{3}+24 = 0} \\\\
y_{1,2} = \frac{6\sqrt{3}\pm \2\sqrt{3}}{2}\\
y_1 = 4\sqrt{3} \quad \text{no solution}\\
y_2 = 2\sqrt{3} \quad \text{solution}\\\\
x = \dfrac{ \sqrt{ 4y^2+6\sqrt{3}y+9 } } {5} \\\\
x = \dfrac{ \sqrt{ 4 (2\sqrt{3})^2+6\sqrt{3}( 2\sqrt{3})+9 } } {5} \\\\
x = \dfrac{ \sqrt{ 48 +36+9 } } {5} \\\\
x = 1.92873015220\\\\
\mathbf{ \overline{BC} =5x = 9.64365076099 }
\end{array}
}$$

 

heureka Jun 24, 2015
 #2
avatar
+13

@heureka/  Your calculations are so impressive!!!

 Jun 24, 2015
 #3
avatar+1069 
+10

    @heureka:/           

                              

 Jun 24, 2015
 #4
avatar+102430 
+10

Great work Heureka

I have added this to the "Great answers to Learn from" sticky thread :)

 Jun 25, 2015
 #5
avatar+575 
0

Great job,Heureka!It,s correct.

Does this question challenge you?

 Jun 25, 2015
 #6
avatar+22484 
+5

Hallo fiora,

yes, this question challange me.

Thank you for this question!

 

 Jun 25, 2015

26 Online Users

avatar
avatar